An Early Dormition Narrative in Karshuni: An Edition and Translation of the “Six Books” Apocryphon from the Karshuni Codex 199 of St Mark’s in Jerusalem (Apograph of Damascus Patr. 12/17 & 12/18) - Shoemaker, Stephen J.; Lamoreaux, John C.; Kaestli, Jean-Daniel (Apocrypha, 2022)
Abstract Le présent article fournit la première édition critique complète d’une forme brève du récit apocryphe de la Dormition de Marie en Six Livres. Un fragment syriaque de cette version était connu depuis 1865 (CANT 121) et était communément considéré comme la forme la plus ancienne de la Dormition en Six Livres et comme dépendant du texte grec du Pseudo-Jean. Le texte arabe karchouni publié ici donne maintenant accès à cette version dans son intégralité. Ce texte a été traduit au xviiie siècle à partir d’un manuscrit syriaque appartenant au Patriarcat syrien orthodoxe de Damas, et la traduction s’avère être très fidèle à son modèle. Outre l’édition du texte karchouni munie d’une traduction anglaise, le présent article inclut une introduction qui cherche à situer cette version particulière au sein de l’histoire de la composition de la Dormition en Six Livres et qui tend à conclure qu’il s’agit d’un résumé d’une forme plus ancienne du récit apocryphe. Un appendice confirme cette conclusion, grâce à une comparaison détaillée entre le texte karchouni et les autres versions syriaques transmises dans des manuscrits de la fin du ve et du vie siècle ; il montre que la version de Damas doit être comprise comme un abrégé et une réécriture d’un texte très proche de la version longue figurant dans le palimpseste de Cambridge édité par Agnes Smith Lewis (CANT 124). Abstract This article presents the first complete critical edition of a short form of the Six Books Apocryphon of the Virgin’s Dormition. A Syriac fragment of this version was known since 1865 (CANT 121) and widely considered as the earliest form of the Six Books Apocryphon and as dependent on the Greek Pseudo-John’s Dormition. The Arabic Karshuni text published here makes this version known in its full extent. It is a translation made in the 18th century from a Syriac manuscript belonging to the Syrian Orthodox Patriarchate in Damascus and it turns out to be a faithful translation of its model. In addition to an edition of the Karshuni text and an English translation, the article also includes an introductory study that seeks to locate this particular version within the literary history of the Six Books Apocryphon and tends to conclude that it is a résumé of some earlier form of the narrative. A concluding appendix confirms this conclusion by comparing in detail the Karshuni version with the other early versions extant in Syriac manuscripts of the late fifth and sixth centuries ; it shows that the Damascus version is best understood as an abbreviation and rewriting of a text which was very close to the long version found in the Cambridge palimpsest edited by Agnes Smith Lewis (CANT 124).